Fabrication and Characterization of a Novel Solid Nano-Dispersion of Emamectin Benzoate with High Dispersibility and Wettability - Ying Li; Qing Wang; Junqian Pan; Xiang Zhao; Jinghui Zhan; Xinglong Xu; Meng Zhang; Chunxin Wang; Haixin Cui (Nanomaterials)
Pesticides, as an indispensable component in agricultural production, play a crucial role in ensuring global food security. However, the low efficiency of pesticide utilization remains a significant challenge. The key method of improving the effective utilization rate of pesticides is mainly to enhance the affinity between pesticides and leaf surfaces while improving their deposition and adhesion properties. In this study, we utilized PEG 4000 as a carrier and emulsifier 600 and emulsifiers 700 as surfactants to prepare solid nano-dispersion of emamectin benzoate (SND-EB) by the melting method. SND-EB particles were spherical with an average diameter of 17 nm, a loading capacity of up to 50%, and excellent dispersibility. Contact angle and bouncing behavior tests on cabbage and pepper leaves demonstrated that SND-EB had superior wetting properties and spreading capabilities. Surface tension and leaf retention measurements further confirmed that SND-EB possessed excellent adhesion and leaf affinity. The SND-EB showed a 1.8-fold increase in biological activity against Spodoptera exigua compared to commercial emamectin benzoate water-dispersible granule (WDG-EB). In addition, the fabricated nanoparticles exerted no toxic effect on HepG2 cells. These results demonstrated that a 50% content of SND-EB exhibited excellent water dispersity, wettability, and insecticidal activity, providing a novel and efficient strategy for pest control.